A viscoelastic model of compression and relaxation behaviors in preforming process for carbon fiber fabrics with binder. (1st February 2019) - Wei, Kai; Liang, Ding; Mei, Ming; Yang, Xujing; Chen, Liming
Abstract: The preforming process of fiber fabrics in liquid composite molding presents remarkable viscoelastic behaviors, and gives significant effect on the overall mechanical properties of composite components. Thus, here, a unified viscoelastic model to predict the compression and relaxation viscoelastic behaviors in preforming process for the carbon fiber fabrics with binder is originally proposed. The physical meaning of each model parameter is rationally defined. Experiments for typical carbon fiber fabrics are conducted to validate the proposed model. The theoretical curves match well with the experimental measurements, and the correlation factors for different contents of binder are larger than 0.9, demonstrating the proposed model can well capture the stress evolution. Besides, we clearly reveal that in compression, the elastic stress is the main stress, and the viscoelastic stress is very small. Elastic modulus increases non-linearly and rapidly with the loading time. As the content of the binder increases, the elastic modulus gradually decreases due to the binder layer. For the relaxation stage, the total stress relaxation ratio is enlarged, while the elastic stress relaxation ratio is reduced, indicating the addition of binder can significantly improve the relaxation ability of the fabrics. The relationship of delay time τ : τ 0 w t < τ 4 w t < τ 8 w t < τ 12 w t is experimentally confirmed, and is consistent with the theoretical prediction, suggesting the increasing binder enlarges the relaxation time. The proposed theoretical model here provides an approach to understand the viscoelastic responses in preforming process.